Soil acidity and nutrient deficiency in central Amazonian heath forest soils - Luizão, Flávio Jesus; Luizâo, Regina Celi Costa; Proctor, John (Plant Ecology, 2007)
Experiments were carried out to test the effects of liming and nutrient additions on plant growth and soil processes such as C and N mineralisation in three contrasting forest types in central Amazonia: the stunted facies of heath forest (SHF), the tall facies of heath forest (THF) and the surrounding lowland evergreen rain forest (LERF). Calcium-carbonate additions increased soil respiration in the field plots in the SHF; in laboratory incubations, soil respiration was higher in the SHF when soils were fertilised with N, and in THF and LERF after S additions. The addition of N alone or in different combinations generally induced a net immobilisation of soil N. Net nitrification increased during the incubation in SHF and THF soils fertilised with N+P, and in LERF soils fertilised with either N, or P, or CaCO3. In a field experiment using ingrowth bags, a higher fine root production was observed in all forest types when bags were fertilised with CaCl2 or CaCO3, suggesting that Ca may be a limiting nutrient in these soils. Calcium-carbonate addition in a glasshouse bioassay experiment with rice showed an overall positive effect on the survival and growth of the seedlings. In other treatments where soil pH was not raised, the rice showed acute toxicity symptoms, poor root and shoot growth and high mortality. Similar results were yielded in a field experiment, using naturally established seedlings in the field plots in SHF, THF and LERF. It is concluded that the acute H+ ion toxicity is a major growth-limiting factor for non-adapted plants in heath forest soils in central Amazonia. © 2007 Springer Science+Business Media B.V.
Keywords: Acid Soil; Forest Soil; Growth; Heathland; Mortality; Nutrient Limitation; Root; Seedling; Soil Chemistry; Survival; Amazonia; South America